2020
DOI: 10.1101/2020.11.06.367078
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular hallmarks of heterochronic parabiosis at single cell resolution

Abstract: Slowing or reversing biological ageing would have major implications for mitigating disease risk and maintaining vitality. While an increasing number of interventions show promise for rejuvenation, the effectiveness on disparate cell types across the body and the molecular pathways susceptible to rejuvenation remain largely unexplored. We performed single-cell RNA-sequencing on 13 organs to reveal cell type specific responses to young or aged blood in heterochronic parabiosis. Adipose mesenchymal stromal cells… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 34 publications
5
26
0
Order By: Relevance
“…To this end, we identified the primary cell types exhibiting these changes and revealed the common and cell-type-specific aging-induced signatures and transcriptional programs that were rescued following parabiosis in the old brains and/or disrupted in the young brains. As corroborated by recent reports, our data provide evidence that heterochronic parabiosis effectively modulates multiple manifestations of canonical aging hallmarks, including altered intercellular communication 79 , loss of proteostasis 115 , defects in mitochondrial dysfunction 68,116118 and cellular senescence 37,107,119,120 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…To this end, we identified the primary cell types exhibiting these changes and revealed the common and cell-type-specific aging-induced signatures and transcriptional programs that were rescued following parabiosis in the old brains and/or disrupted in the young brains. As corroborated by recent reports, our data provide evidence that heterochronic parabiosis effectively modulates multiple manifestations of canonical aging hallmarks, including altered intercellular communication 79 , loss of proteostasis 115 , defects in mitochondrial dysfunction 68,116118 and cellular senescence 37,107,119,120 .…”
Section: Discussionsupporting
confidence: 89%
“…Collectively, our gene expression matrices provide unprecedented data that can be further explored to form working hypotheses for follow-up studies. Similar to other recent reports 118,123,133 , our study advances fundamental understanding of the mechanisms underlying the aging process and potential interventions that go beyond descriptive studies of cell states. Our work extends current knowledge regarding the effects of heterochronic parabiosis on the aging process and supports the key role of the brain vasculature in mediating these effects.…”
Section: Discussionsupporting
confidence: 81%
“…Palovics et al. investigated inter‐organ and inter‐cellular heterogeneity of transcriptomic profiles in response to heterochronic parabiosis, an approach to exchange blood from young to old or vice versa, and provided solid evidence and new insights for understanding systemic responses and molecular networks among blood‐borne factors and cells at single‐cell solution 20 . Deep understanding of heterochronic parabiosis can characterise biological functions and the therapeutic potential of blood‐borne circulating factors in the body, multiple organs and organelle interactions of ageing.…”
Section: Figurementioning
confidence: 99%
“…Deep understanding of heterochronic parabiosis can characterise biological functions and the therapeutic potential of blood‐borne circulating factors in the body, multiple organs and organelle interactions of ageing. scRNA‐seq data of 20 organs demonstrated that responses to young and aged blood is cell type‐specific in heterochronic parabiosis, where adipose mesenchymal stromal cells, haematopoietic stem cells and hepatocytes were most responsive 20 . scRNA‐seq showed that transcriptomic alterations of skeletal stem cells in ageing were accompanied by transformation of the bone marrow niche and functional decline 21 .…”
Section: Figurementioning
confidence: 99%
“…wealth of insight into the diversity of cell types in these organisms, how related cell types across different tissues are similar or different, how cells change with age, and what are the evolutionary relationships between different cell types across organisms. For example, the Tabula Muris Senis has helped us understand at a global level how gene expression changes with age, which cell types are most affected, and which of these aspects are reversible via rejuvenation approaches such as parabiosis [33,39]. As another example, the Tabula Drosophila has helped reveal how gene expression depends on sex, and has identified which cell types have the highest levels of sex-biased gene expressionthis is a launching pad to help understand how these differences meet the distinct developmental and physiological needs of males and females [31].…”
Section: Outstanding Questionsmentioning
confidence: 99%